Coupled Diffusion and Oxidation of Ferrous Iron in Soils. III. Further Development of the Model and Experimental Testing - Kirk, G.J.D.; SOLIVAS, J.L. (Wiley, 1994)
Equations are developed to predict the distribution of Fe2+ between solid and solution phases in a reduced soil undergoing oxidation at different pHs, based on cation‐exchange equilibria and electrical neutrality in the solid and solution. The equations satisfactorily explained experimental results. They are incorporated in the model of Fe2+ diffusion and oxidation developed in Part II, and the model is also extended to allow for O2 consumption in processes other than Fe2+ oxidation. The resultant predictions are tested against measured profiles of Fe(II), Fe(III) and pH in cylinders of reduced soil exposed to O2 at one end. When oxidation rate constants measured in stirred soil suspensions were used to run the model, the predicted rates of O2 consumption were too great and the spread of the oxidation front too small. Satisfactory agreement was achieved for oxidation rate constant values about one‐eighth of those measured in the stirred suspensions. The findings are consistent with the rate of Fe2+ oxidation in soil being controlled by access of O2 to Fe2+ sorption sites, as suggested in Part I. The revised model allows a study of the effects of Fe2+ oxidation on the mobility of other cations in reduced soils, e.g. nutrient cations in the rice rhizosphere. Fez+ oxidation and the accompanying acidification may greatly impede cation mobility in reduced soils.